Normalizing library records display using FRBR model for al-Qur'an work-set - Abdul Aziz, Normaziah; Mansor, Yushiana; Sarif Abdullah, Sharifah Nur Amirah; Mohd Shah, Siti Raihana; Aersid, Nurul Farhana (IEEE, 2014)
The Functional Requirements for Bibliographic Records (FRBR) model is a conceptual entity-relationship model developed for better arrangement, collocation, and navigation in bibliographic databases. As such, a FRBRized library online catalog (OPAC) can improve the performance of OPAC as a retrieval tool. We explored the utility of FRBR framework for supporting rich indexation, and rich interaction in digital libraries using an open source FRBR tool developed by the Library of Congress. We tested the system on some MARC-based bibliographic records from the International Islamic University Malaysia (IIUM) library. Several issues have been found useful to be explored which includes multi-script, complex work, and missing fields. We also experimented on FRBRzing the work-set on al-Quran using the LOC FRBR Display Tool. This paper will elaborate on the process of FRBRizing using this open-source tool. Several problems encountered in the experiment are discussed and future enhancements are proposed. This work may initiate interest among the librarian to adopt FRBR as advancement to the existing digital library system.